The Irony of the Cranes: Labour Issues in the Construction Industry in the New China - Charles S. Costello III (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
The crane has been an ancient symbol of longevity in China carrying with it intimation of distinctive principles of ancient China; harmony, patience and graceful coexistence with nature. It is ironic that the construction crane is the new symbol of a changing land, where old hutong neighborhoods are disappearing as fast as the bird and its habitat. Is this new crane helping to create a harmonious society, as the HuWen administration would have you believe? The economic boom fueled in large part by the 2008 Beijing Olympic Games brings with it many new construction jobs, labour issues and in some cases new forms of corruption. Does this development reinforce solidarity and good working conditions in a country where unions are largely controlled by the government? Or do business networks, guanxi, continue to dominate business relationships and hamper the achievement of good working conditions? These questions will be examined, including issues such as corruption, safety and working conditions. Comparisons to labour issues in the United States will be included.
hdl:10398/8944
Keywords: 330; Labour; China; Olympics; Construction; Crane